Pengujian Technology Accepted Model and Perceived Cost of Use Terhadap Penggunaan Sistem Em-Pise Pada LPD Desa Adat Tunjuk - Ni Kadek Krisna Dewi; I Putu Gede Diatmika (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
Lembaga Perkreditan Desa is a financial institution that implements the use of information technology systems as one of the competitive advantages with other banking companies. One of the technology systems implemented is e-banking where the public is able to make payments more easily and practically anywhere and anytime. Lembaga Perkreditan Desa of Adat Tunjuk Village is one that implements an e-banking system called Em-pise. However, due to the lack of customer understanding of some features that are difficult to use, the Lembaga Perkreditan Desa of Tunjuk must review the use of the Em-pise system.This study aims to determine the variable perceptions of ease, perceived usefulness, user interest and user costs for the implementation of the em-pise system. The researchmmethod used in the study is a quantitative researchmmethod withp rimary data obtained from questionnaire data measured using a Likert scale. This research was conducted at the Adat Tunjuk Village Credit Institute. The population in this study were 5,246 LPD customers. The sampling method is done by simple random sampling and the number of samples is 98 people. The research data was collected using a question aire which was then processed using multiple linear regression tests with the help of SPSS 20. The results of this study stated that the variable system user efficacy (X1), the system user convenience variable (X2), the variable of user interest in the system (X3), the variable system user cost (X4) has a positive and significant effect on the use oftthe em-pise system (Y). This research implies that the customers of Adat Tunjuk Village Credit Institutions are expected to increase perceptions related to the utility and ease of technology, hence there will be an interest that influences customers to apply payments online so that customers are able to increase the use of the em-pise system and also support the efforts made by employee of Lembaga Perkreditan Desa.